Studi In-Vitro Antikolesterol dari Fraksi Etil Asetat Daun Buni Antidesma bunius L. Spreng - Thoha Irfan Darojat; Danang Raharjo; Bagas Ardiyantoro (Jurnal Kesehatan Amanah, 2026)
Hypercholesterolemia, defined as elevated levels of cholesterol in the bloodstream, is widely recognized as a major risk factor for cardiovascular diseases, including atherosclerosis and coronary heart disease. Antioxidants play an important role in preventing oxidative damage by neutralizing free radicals through electron donation, thereby helping to reduce lipid peroxidation associated with high cholesterol levels. This study aims to evaluate the cholesterol-lowering activity of the ethyl acetate fraction of buni leaves (Antidesma bunius) through laboratory experimentation. The leaves were extracted using the maceration method with 96% ethanol, followed by fractionation with ethyl acetate to obtain the targeted fraction. The in vitro anticholesterol activity was determined using the Liebermann–Burchard method and measured by UV-Vis spectrophotometry. Data analysis was performed using linear regression to calculate the IC₅₀ value. The results demonstrated that the ethyl acetate fraction exhibited very strong cholesterol-lowering activity, with an IC₅₀ value of 1,659 ppm/µg/mL, indicating promising potential as a natural antihypercholesterolemic agent.